Analisis Air Buangan Kantin di Kampus II Universitas Bhayangkara Jakarta Raya: Analisis, limbah domestik, software Montecarlo, Crystall ball, Predictor - Lisa Adhani; Wahyu Kartika; Dovina Navanti (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2020)
Canteen is a producer of domestic liquid waste that has the potential to cause pollution. Likewise with the student canteen, it has the potential to produce waste that causes environmental pollution if it is not treated properly. The use of Montecarlo software in this study is to support quantitative analysis in predicting potential pollution from Ubhara canteen waste with Crystall ball prediction. The results of laboratory analysis in the form COD, BOD dan TSS, showed that the quality of the canteen waste water did not meet the requirements for wastewater quality standard based on Ministry of Environment Decree No. 112 of 2003. Supported by the results of CB Predictor simulations showing the potential of pollution of the Ubhara canteen waste water to the environment continues to increase significantly, also seen from the Double Exponential Smoothing Method, producing MAD (Mean Absolute Deviation) 170.82, Theil's U 0.9951, and Confidence Interval Lower 5% and Upper 99.5%.